EFEKTIVITAS PENGGUNAAN APLIKASI MARHANI GROCERY ONLINE DALAM MEMENUHI KEBUTUHAN POKOK (SEMBAKO) RUMAH TANGGA MASYARAKAT TIMIKA - Saina; Nely Salu Padang (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This study aims to determine the level of effectiveness of the Marhani Grocery Online app. The research method used is a descriptive method. In this study, the data collection technique used was a questionnaire. To determine the level of effectiveness of the Marhani Grocery Online app, the analytical tool employed was frequency distribution analysis. The results of this study indicate that all three factors—namely, the level of trust, which showed an effectiveness of 94%, ease of use showed an effectiveness of 95%, and benefits of use showed an effectiveness of 95%. It can therefore be concluded that all three factors were confirmed to have an effectiveness level in the use of the Marhani Grocery Online app of 95%, with ease of use and benefits of use having the highest effectiveness levels at 95%.